Mechanisms of Mechanical Force Induced Pulmonary Vascular Endothelial Hyperpermeability - Lai, Yan; Huang, Yongbo (Frontiers in Physiology, 2021)
Mechanical ventilation is a supportive therapy for patients with acute respiratory distress syndrome (ARDS). However, it also inevitably produces or aggravates the original lung injury with pathophysiological changes of pulmonary edema caused by increased permeability of alveolar capillaries, composed of microvascular endothelium, alveolar epithelium, and basement membrane. Vascular endothelium forms a semi-selective barrier to regulate body fluid balance. Mechanical ventilation in critically ill patients produces a mechanical force on lung vascular endothelium then the endothelial barrier was destructed. This review aims to provide a comprehensive overview of molecular and signaling mechanisms underlying the endothelial barrier permeability after mechanical ventilation or cyclic stretch.